ORTHODOX LANDSCAPE OF THE TYUMEN REGION: LOCATION, NUMBER AND DEMOGRAPHIC COMPOSITION OF URBAN PRAYER MEETINGS - I.V. Bobrov; M.S. Cherepanov; A.L. Shisheliakina (Вестник археологии, антропологии и этнографии, 2019)
Description of regional Orthodox landscapes has been one of the crucial tasks of religious studies in Russia. Despite the growing number of publications on this issue, researchers make a point that this work should be con-tinued in order to identify changes in the characteristics under consideration. The present article was written on the basis of field research conducted in Tyumen, Ishim and Yalutorovsk (Tyumen region, Russia) in 2015–2016 and covers the location, number and demographic composition of Orthodox prayer meetings. In this work, we provide data on the city of Tyumen (including information on churches that have been erected there since 2009), as well as present materials on Ishim and Yalutorovsk for the first time. In addition, we demonstrate changes in the Orthodox landscape of the regional centre using the results of research conducted in Tyumen from 2005 to 2009. In the course of field research, non-participant structured observation was used as the main method, with analysis of Orthodox mass media being used to refine the obtained data. The results show a positive dynamics in the number of faith practitioners in Tyumen. In this work, we described the demographic composition of believers in three cities of the region and determined factors affecting the distribution of believers among urban churches. The number of parishioners in Tyumen churches has increased by more than one and a half times at ferial Sun-day liturgies; almost by two times on Palm Sundays; and by a quarter at the Easter services. This growth is asso-ciated with the distribution of the increased urban population among new churches built near the expanding resi-dential areas of the regional centre. It should be noted that women of middle and advanced age still constitute the largest demographic groups at urban collective services. In comparison with Tyumen, the churches of Yalutorovsk and Ishim are attended by a higher percentage of elderly parishioners. The main factors affecting the church at-tendance include the status of a church in the Orthodox hierarchy, the church’s capacity and its location. Most well-attended churches are situated in the downtown, have a special status (cathedral church, Stauropegic church, a church on the territory of an eparchial monastery) and are more spacious.